Pathway analysis of microarray data from corpora cavernosal tissue of patients with a prostatectomy or Peyronie disease in comparison with a cavernous nerve–injured rat model of erectile dysfunction. (12th January 2023) - Searl, Tim; Ohlander, Samuel; McVary, Kevin T; Podlasek, Carol A
Abstract: Introduction: Patients with a prostatectomy are at high risk of developing erectile dysfunction (ED) that is refractory to phosphodiesterase type 5 inhibitors. The cavernous nerve (CN) is frequently damaged during prostatectomy, causing loss of innervation to the penis. This initiates corpora cavernosal remodeling (apoptosis and fibrosis) and results in ED. Aim: To aid in the development of novel ED therapies, the current aim was to obtain a global understanding of how signaling mechanisms alter in the corpora cavernosa with loss of CN innervation that results in ED. Methods: Microarray and pathway analysis were performed on the corpora cavernosal tissue of patients with a prostatectomy (n = 3) or Peyronie disease (control, n = 3). Results were compared with an analysis of a Sprague-Dawley rat CN injury model (n = 10). RNA was extracted by TRIzol, DNase treated, and purified by a Qiagen Mini Kit. Microarray was performed with the Human Gene 2.0 ST Array and the RU34 rat array. Differentially expressed genes were identified through several analytic tools (ShinyGO, Ingenuity, WebGestalt) and databases (GO, Reactome). A 2-fold change was used as the threshold for differential expression. Outcomes: Pathways that were altered (up- or downregulated) in response to CN injury in the prostatectomy patients and a rat CN injury model were determined. Results: Microarray identified 197 differentially expressed protein-coding genes in the corpora cavernosa from the prostatectomy cohort, with 100 genes upregulated and 97 genes downregulated. Altered signaling pathways that were identified that affect tissue morphology included the following: neurologic disease, cell death and survival, tissue and cellular development, skeletal and muscle development and disorders, connective tissue development and function, tissue morphology, embryonic development, growth and proliferation, cell-to-cell signaling, and cell function and maintenance. These human pathways have high similarity to those observed in the CN-injured rat ED model. Clinical Implications: Significant penile remodeling continues in patients long after the acute surgical injury to the CN takes place, offering the opportunity for clinical intervention to reverse penile remodeling and improve erectile function. Strengths and Limitations: Understanding how signaling pathways change in response to CN injury and how these changes translate to altered morphology of the corpora cavernosa and ensuing ED is critical to identify strategic targets for therapy development. Conclusion: Altered signaling in pathways that regulate tissue homeostasis, morphogenesis, and development was identified in penes of patients with a prostatectomy, and competitive forces of apoptosis and proliferation/regeneration were found to compete to establish dominance after CN injury. How these pathways interact to regulate penis tissue homeostasis is a complex process that requires further investigation.